Kontribusi Usahatani Kakao terhadap Pendapatan Rumah Tangga Petani Di Desa Watumelewe Kecamatan Iwoimendaa Kabupaten Kolaka - Aan Wilhan Juliatmaja; Helviani Helviani (Journal of Food System & Agribusiness, 2022)
This research was conducted with the aim of knowing the significance of the percentagecontribution of cocoa farming to the total household income of farmers in Watumelewevillage, Iwoimendaa district, Kolaka regency. This research was conducted using bothqualitative and quantitative methods, the contribution of revenue is analyzed by calculatingthe percentage contribution/contribution revenue (%). Based on the results of the study, itwas reported that the average farmer income from cocoa farming was IDR 5.510.000 andthe contribution of farm household income from cocoa farming is 49,41% which is includedin the medium category.